2012
DOI: 10.1103/physrevb.85.064104
|View full text |Cite
|
Sign up to set email alerts
|

Regular nanodomain vertex arrays in BiFeO3single crystals

Abstract: Domain patterns consisting of triangular nanodomains of less than 50 nm size, arranged into long regular vertex arrays separated by stripe domains, were observed by (scanning and high-resolution) transmission electron microscopy and piezoresponse force microscopy in BiFeO 3 single crystals grown from solution flux. Piezoresponse force microscopy analysis together with crystallographic analysis by selected area and nanobeam electron diffraction indicate that these patterns consist of ferroelectric 109 • domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…The actual symmetry as well as the origin of these domains remains to be determined. Of particular relevance here is the transmission electron microscopy study of Berger et al, 21 performed on the same type of samples. These authors see strikingly similar domain patterns to those reported here, even though the plane orientation of their TEM samples, (110), is different from those in the PFM study, (001).…”
Section: Discussionmentioning
confidence: 99%
“…The actual symmetry as well as the origin of these domains remains to be determined. Of particular relevance here is the transmission electron microscopy study of Berger et al, 21 performed on the same type of samples. These authors see strikingly similar domain patterns to those reported here, even though the plane orientation of their TEM samples, (110), is different from those in the PFM study, (001).…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Calculations 22 attribute their formation and stabilization to competition between long-and short-range electrostatic forces. The same domain configuration was reported in TEM specimens that were not confined to a capacitor-like geometry 20,21 and in bulk polished samples for piezoresponse force microscopy. 20 Jia et al 21 performed a comprehensive atomic-resolution investigation of this type of DW in BFO single crystals, employing negative spherical aberration imaging TEM techniques.…”
mentioning
confidence: 99%
“…The crystals were harvested from the flux using diluted (10%) HNO 3 and further processed by polishing. The structural properties and domain pattern of typical crystals have been previously reported . Crystal C4 is similar (same batch and processing) to the crystal used by Alexe and Hesse .…”
Section: Methodsmentioning
confidence: 79%